Developing a Model for Geomorphological Hazards in the Tangro Valley Basin Using RS & GIS (Journal of the College of Basic Education, 2025)
The study aims to develop a spatial model to identify and assess geomorphological hazards using RS and GIS techniques in the Tangro Valley Basin, located in Sulaymaniyah Governorate. The research problem lies in the fact that the Tangro Valley Basin is exposed to various geomorphological hazards. Therefore, the study seeks to answer the question: How can a scientific spatial model be built to identify and evaluate these hazards in order to achieve more accurate predictions of high-risk areas?, The model construction follows multiple methodological steps, beginning with assigning relative weights to each geomorphological factor based on its relative importance and expected impact. Then, internal weights were determined by classifying each factor into three levels of risk (low, medium, high), and assigning them numerical values of (1, 2, 3) respectively, The results revealed that 12.1% of the basin area falls within the high-risk zones, which are concentrated in the northeastern and northwestern parts of the Tangro Valley Basin, characterized by steep slopes. Additionally, 85.9% of the basin area lies within the medium-risk zone, while only 2% of the total basin area is classified as low-risk, mostly located in the eastern part of the study area near Lake Darbandikhan, The spatial analysis also revealed an overlap between high-risk areas and human settlements, as approximately 20.7% of the villages and residential clusters are located within these zones.